Sensitization to reactive diluents and hardeners in epoxy resin systems: IVDK data 2002-2011$dpart I: reaction frequencies - Geier, Johannes; Lessmann, Holger; Hillen, Uwe; Skudlik, Christoph; Jappe, Uta (Contact dermatitis, 2016)
BACKGROUND: Epoxy resin systems (ERSs), consisting of resins, reactive diluents, and hardeners, are indispensable in many branches of industry. In order to develop less sensitizing ERS formulations, knowledge of the sensitizing properties of single components is mandatory. - OBJECTIVES: To analyse the frequency of sensitization in the patients concerned, as one integral part of a research project on the sensitizing potency of epoxy resin compounds (FP-0324). - METHODS: A retrospective analysis of data from the Information Network of Departments of Dermatology (IVDK), 2002-2011, and a comparison of reaction frequencies with (surrogate) exposure data, were performed. - RESULTS: Almost half of the patients sensitized to epoxy resin were additionally sensitized to reactive diluents or hardeners. Among the reactive diluents, 1,6-hexanediol diglycidyl ether was the most frequent allergen, followed by 1,4-butanediol diglycidyl ether, phenyl glycidyl ether, and p-tert-butylphenyl glycidyl ether. Among the hardeners, m-xylylene diamine (MXDA) and isophorone diamine (IPDA) were the most frequent allergens. According to the calculated exposure-related frequency of sensitization, MXDA seems to be a far more important sensitizer than IPDA. Up to 60% of the patients sensitized to hardeners and 15-20% of those sensitized to reactive diluents do not react to epoxy resin. - CONCLUSIONS: In cases of suspected contact allergy to an ERS, a complete epoxy resin series must be patch tested from the start.
First published: 05 November 2015
Gesehen am 22.05.2020